2013
DOI: 10.15690/vsp.v12i2.618
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection. Pathogenesis Peculiarities, Prevention and Treatment Strategies

Abstract: Научно-исследовательский институт гриппа, Санкт-Петербург, Российская Федерация ВВЕДЕНИЕ Респираторно-синцитиальный вирус (РСВ) занимает существенное место в структуре инфекционной патоло-гии дыхательного тракта, в особенности у детей первых лет жизни. 70% детей переносят РСВ-инфекцию (РСВИ) в возрасте до 1 года, и практически каждый инфици-руется в течение первых двух лет жизни. К двум годам приблизительно 50% детей переносят РСВИ дважды. В развитых индустриальных странах у детей в возрасте до 3 лет, госпита… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…At the same time, clinical trials have not found sufficient evidence of ribavirin efficacy in the treatment of HRSV infection in children less than 1 year of age. In addition, ribavirin is a toxic medication and, hence, indications for its inhalation include severe laboratory-confirmed HRSV infection in young children and patients with congenital heart disease [ 31 ].…”
Section: Pneumovirusesmentioning
confidence: 99%
“…At the same time, clinical trials have not found sufficient evidence of ribavirin efficacy in the treatment of HRSV infection in children less than 1 year of age. In addition, ribavirin is a toxic medication and, hence, indications for its inhalation include severe laboratory-confirmed HRSV infection in young children and patients with congenital heart disease [ 31 ].…”
Section: Pneumovirusesmentioning
confidence: 99%
“…Having a high level of clinical manifestation severity (severe bronchiolitis and pneumonia, which may lead to death) in babies and young children, RSV infection is a significant medical and social problem nowadays [ 1 ]. Risk groups for RSV infection are also people over 65 years of age and patients with weakened immunity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In children under five years of age, RSV causes more than 30 million cases of acute lower respiratory tract infection per year; 3.2 million of them are severe and require hospitalization [ 8 ]. Among children hospitalized with RSV infection, mortality averages 1%, but reaches 37% with a burdened history [ 9 ]. In children under three years of age, RSV is the cause of 50–90% of bronchiolitis, 5–40% of pneumonia, and 10–30% of tracheobronchitis.…”
Section: Introductionmentioning
confidence: 99%